2019
DOI: 10.3130/aija.84.1463
|View full text |Cite
|
Sign up to set email alerts
|

On the Dimensional Plan in Prasat Sambor Monuments in Sambor Prei Kuk Monuments

Abstract: Monuments was functioned as huge-scale heritage of city between Pre-Angkor period and Angkor-Period.Recent studies about dimensional planning of times in Angkor-Period are achieved certain result. On the other hand, the study about the sites planned in temple area of Sambor Prei Kuk Monuments is not abundance. The importance of these monuments is clear from these monuments are considered as " 伊奢那城 " that was capital of Chenla. The purpose of this study is revealing the basic dimensional plan system of these mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The current results by his team indicated that the true length of a hasta was 412 mm (Mizoguchi et al, 2007(Mizoguchi et al, , 2009(Mizoguchi et al, , 2010a(Mizoguchi et al, , 2010b(Mizoguchi et al, , 2012. Based on the analysis of each shrine in Sambor Prei Kuk, the construction unit for individual shrines were estimated to be around 407.5 mm (Narui et al, 2019). The authors suggested that the construction unit varied between monuments, even though these monuments belong to the same temple complex.…”
Section: Analyzing the Planning Technique Behind Prasat Sambormentioning
confidence: 80%
“…The current results by his team indicated that the true length of a hasta was 412 mm (Mizoguchi et al, 2007(Mizoguchi et al, , 2009(Mizoguchi et al, , 2010a(Mizoguchi et al, , 2010b(Mizoguchi et al, , 2012. Based on the analysis of each shrine in Sambor Prei Kuk, the construction unit for individual shrines were estimated to be around 407.5 mm (Narui et al, 2019). The authors suggested that the construction unit varied between monuments, even though these monuments belong to the same temple complex.…”
Section: Analyzing the Planning Technique Behind Prasat Sambormentioning
confidence: 80%